2020
DOI: 10.1021/acschemneuro.0c00003
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of New (2S,3R)-3-Carboxyphenyl)pyrrolidine-2-carboxylic Acid Analogues Utilizing a C(sp3)–H Activation Strategy and Structure–Activity Relationship Studies at the Ionotropic Glutamate Receptors

Abstract: Competitive antagonists for ionotropic glutamate receptors (iGluRs) are highly valuable tool compounds for studying health and disease states in the central nervous system. However, only few subtype selective tool compounds are available and the discovery of antagonists with novel iGluR subtype selectivity profiles remains a profound challenge. In this paper, we report an elaborate structure–activity relationship (SAR) study of the parental scaffold 2,3-trans-3-carboxy-3-phenyl-proline by the synthesis of 40 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The antagonists ATPO and UBP282 bind AMPA receptor subunits as well as GluK1 (Moller et al, 1999;Dolman et al, 2005) (Supplemental Tables 8 and 9). A series based on the antagonist (2S,3R)-3-(3-carboxyphenyl)-pyrrolidine-2-carboxylic acid was designed to be nonselective among all glutamate-binding iGluR subunits (Larsen et al, 2011a) and included competitive antagonists with preference for GluK3 over GluK1 and AMPA receptor subunits (Krogsgaard-Larsen et al, 2015), GluK1 selectivity (Krogsgaard-Larsen et al, 2017), and selectivity for NMDA receptors over AMPA and kainate receptors (Kayser et al, 2020) (Supplemental Tables 8 and 9). A class of heterotricyclic glutamate analogs combined structural elements of kainate and neodysiherbaine A, resulting in IKM-159 with selectivity for AMPA receptors (Gill et al, 2010;Juknait_ e et al, 2013).…”
Section: B Competitive Antagonistsmentioning
confidence: 99%
“…The antagonists ATPO and UBP282 bind AMPA receptor subunits as well as GluK1 (Moller et al, 1999;Dolman et al, 2005) (Supplemental Tables 8 and 9). A series based on the antagonist (2S,3R)-3-(3-carboxyphenyl)-pyrrolidine-2-carboxylic acid was designed to be nonselective among all glutamate-binding iGluR subunits (Larsen et al, 2011a) and included competitive antagonists with preference for GluK3 over GluK1 and AMPA receptor subunits (Krogsgaard-Larsen et al, 2015), GluK1 selectivity (Krogsgaard-Larsen et al, 2017), and selectivity for NMDA receptors over AMPA and kainate receptors (Kayser et al, 2020) (Supplemental Tables 8 and 9). A class of heterotricyclic glutamate analogs combined structural elements of kainate and neodysiherbaine A, resulting in IKM-159 with selectivity for AMPA receptors (Gill et al, 2010;Juknait_ e et al, 2013).…”
Section: B Competitive Antagonistsmentioning
confidence: 99%
“…Ease of AQ removal in these cases once again depends on the accessibility of the amide bond which can be strongly influenced by the size of substituents on the ring nitrogen (Scheme 13). While a direct comparison of substituent size on AQ‐hydrolysis has not been published in the literature, the following trends can be deduced from selected examples: While Boc‐ and Piv‐protection did not impede AQ removal ( 85 – 86 ), [66, 67] Cbz‐protection adjacent to the AQ‐amide made it highly resistant to hydrolysis ( 83 – 84 ) [68] . In this case, the directing group had to be modified to the more reactive 5‐methoxy‐8‐amino‐quinoline (MQ) derivative for successful removal (see Section 2.2).…”
Section: Nucleophilic Cleavage Of the Amide Bondmentioning
confidence: 99%
“…An alternative method involved 2,3- cis - l -proline 16 , which has previously been synthesized via a C­(sp 3 )-H activation approach by Chen et al We therefore saw a productive combination of this work and our recently reported stereoselective synthesis of a series of 2,3- trans -3-aryl l -prolines by an α-epimerization approach, to obtain key alkyne 2 (Scheme ).…”
Section: Resultsmentioning
confidence: 89%
“…Next, transformation of iodide 11 via iron-catalyzed cross-coupling to in situ prepared TMSprotected alkynyl Grignard reagent was tried, but failed to deliver the desired product 13. 20 An alternative method involved 2,3-cis-L-proline 16, which has previously been synthesized via a C(sp 3 )-H activation approach by Chen et al 21 We therefore saw a productive combination of this work and our recently reported stereoselective synthesis of a series of 2,3-trans-3-aryl L-prolines by an α-epimerization approach, 12 to obtain key alkyne 2 (Scheme 2).…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation